Ketogenic Diet and Gut Microbiota: Exploring New Perspectives on Cognition and Mood - Yuhan Jiang; Yili Chen; Youmeng Chen; Xinrong Gong; Zhiyu Chen; Xin Zhang (Foods)
The ketogenic diet (KD) is a dietary regimen characterized by low carbohydrate intake and moderate protein levels, designed to simulate a fasting state and induce ketosis for the production of ketone bodies from fat. Emerging research underscores KD’s potential in improving cognitive functions and regulating mood. Investigations into its safety and efficacy have centered on its anti-inflammatory properties and its impact on neurological health and the gut–brain axis (GBA). This review delves into the relationship between the KD and gut microbiota, emphasizing its potential role in cognitive enhancement and mood stabilization, particularly for managing mood disorders and depression. The investigation of the KD’s physiological effects and its role in promoting cognition and emotion through gut microbiota will pave the way for innovative approaches to personalized dietary interventions.